Teachers' Grading Practices: In Search for Clear Grading Criteria - Zulaiha, Siti (University of Muhammadiyah Prof. DR. HAMKA, 2017)
Grading is a complicated process yet serves many significant roles such as judging students' achievement and providing parental feedback. However, studies suggest that grading practices are not always uniform in that non-achievement factors are also frequently included in determining grades. Thus it is important to review and further understand teachers' grading practices. This article explores the discussion and debates around grading practices both in the general education field as well as studies in the English as a foreign language (EFL) context. The discussion, in particular, focuses on the range of factors that influence teachers' grading practices. Finally, this article reflects on implications of grading practices and offers suggestions that have been commonly recommended by experts.